2009
DOI: 10.1073/pnas.0907147106
|View full text |Cite
|
Sign up to set email alerts
|

DNA polymerase ε and δ proofreading suppress discrete mutator and cancer phenotypes in mice

Abstract: Organisms require faithful DNA replication to avoid deleterious mutations. In yeast, replicative leading-and lagging-strand DNA polymerases (Pols and ␦, respectively) have intrinsic proofreading exonucleases that cooperate with each other and mismatch repair to limit spontaneous mutation to less than 1 per genome per cell division. The relationship of these pathways in mammals and their functions in vivo are unknown. Here we show that mouse Pol and ␦ proofreading suppress discrete mutator and cancer phenotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
221
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(241 citation statements)
references
References 34 publications
11
221
2
Order By: Relevance
“…Indeed, in the yeast mutants in which pol delta or epsilon proofreading is selectively inactivated, the mutations rates are 10-100 times higher than the wild-type strains. [26][27][28] Recently, mice carrying artificial alleles with substitutions at essential amino-acid residues in the proofreading domains of pol delta 29,30 and epsilon 31 have been reported. The observed mutation rates were indeed significantly elevated over the wild-type levels.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in the yeast mutants in which pol delta or epsilon proofreading is selectively inactivated, the mutations rates are 10-100 times higher than the wild-type strains. [26][27][28] Recently, mice carrying artificial alleles with substitutions at essential amino-acid residues in the proofreading domains of pol delta 29,30 and epsilon 31 have been reported. The observed mutation rates were indeed significantly elevated over the wild-type levels.…”
Section: Introductionmentioning
confidence: 99%
“…A homozygous knockout of these polymerases results in embryonic lethality [Overbeek et al, 2011;Glodsby et al, 2001Glodsby et al, , 2002Uchimura et al, 2009]. Defects in the exonuclease proofreading activity result in increased incidence of malignancies and cardiac abnormalities [Goldsby et al, 2001[Goldsby et al, , 2002Albertson et al, 2009;Uchimura et al, 2009]. Defects in the polymerase activity of Pol d resulted in an increased incidence of cancer and cardiomyopathy [Venkatesan et al, 2007].…”
Section: The B Family Of Dna Polymerasesmentioning
confidence: 99%
“…In the case of Pole e /Mlh1 mice, homozygous mutant mice were present at normal ratios upto E14.5 but none survived after weaning. The Pole e /Msh2 homozygous mutation resulted in complete postnatal lethality with no mice surviving at weaning [Albertson et al, 2009].…”
Section: Dna Polymerase Epsilon (Pol E)mentioning
confidence: 99%
“…4 Furthermore, tumors with POLE exonuclease lacked MLH1 silencing, which is consistent with findings from mouse models that POLE EDMs are mutually exclusive and are incompatible with the complete loss of mismatch repair (MMR). 6 However, it has been reported that several endometrial and colon tumors with POLE EDMs harbor mutations in MMR genes, although the functional significance of these mutations is uncertain, particularly in the setting of an MSS phenotype. 4 In this issue of Cancer, Billingsworth and colleagues present data challenging the notion that POLE EDMs are associated with an MSS phenotype in endometrial cancer.…”
mentioning
confidence: 99%
“…Although POLE mutations were significantly more common in MSI tumors that lacked MLH1 methylation, the authors reported 4 tumors with both POLE mutations and MLH1 silencing; this was an unexpected finding, because previous reports have suggested that MLH1 silencing and POLE EDMs are mutually exclusive. 4,6 POLE EDMs were identified in 8 MSI tumors without MLH1 silencing, and the authors examined 3 of these tumors using immunohistochemistry (IHC) for DNA MMR protein expression. Two of the 3 tumors lacked 1 or more MMR proteins and harbored somatic mutS homolog 6 (MSH6) mutations but had no germline MMR mutations.…”
mentioning
confidence: 99%